Distributed Averaging Problems of Agriculture Picking Multi-Robot Systems via Sampled Control - Ma, Fengying; Yao, Hui; Du, Mingjun; Ji, Peng; Si, Xiaoan (Frontiers in Plant Science, 2022)
Distributed control of multi-agent systems have been widely used in the field of smart agriculture, this paper aims to explore the distributed problems of agriculture picking multi-robot systems under directed communication topologies by taking advantage of the sampled control method. With the algebraic graph theory concepts and the consensus theory, to improve the redundancy and robustness of agricultural multi-agent systems, a distributed protocol is proposed based on the nearest sampled neighbor information. It is shown that under the proposed protocol, the states of all agents can be guaranteed to reach consensus whose value is the averaging of initial states of all agents. Besides, when considering time-delay, the other distributed protocol is constructed, in which a time margin of the time-delay can be determined simultaneously. The necessary and sufficient consensus results can be developed even though the existence of time delay. Simulation results are given to demonstrate the effectiveness of our developed consensus results.